Psychophysiological and psychological responses of touching plant behavior by tactile stimulation according to the foliage type - Seo-Hyun Kim; Sin-Ae Park (PLoS ONE, 2025)
Urbanization-related stress has spurred interest in natural therapies, such as horticultural therapy, which leverages multisensory exposure to plants to enhance well-being through physical, psychological, and cognitive benefits. This study aimed to measure and compare the psychophysiological and psychological responses to tactile stimuli through plant contact based on the foliage type. Thirty adults (average age: 24.86 ± 2.68) participated in the study, and the foliage was categorized into four groups: soft (e.g., Stachys byzantina, Adiantum raddianum, and Asparagus plumosus var. nanus), smooth (e.g., Peperomia obtusifolia, Ficus benghalensis, and Epipremnum aureum), stiff (e.g., Chamaeshparis thyoides Red Star, Platycladus orientalis, and Cupressus macrocarpa), and rough (e.g., Rhapis excelsa, Nephrolepis cordifolia ‘Duffii’, and Ardisia pusilla ‘Variegata’) plant groups. The participants touched the plants for 90 s, and the concentration of oxyhemoglobin (oxy-Hb) in the prefrontal cortex (PFC) was measured using functional near-infrared spectroscopy (fNIRS). Additionally, a semantic differential method (SDM) evaluation tool was used to assess the psychological responses of each treatment group. When comparing the four tactile treatment groups (soft, smooth, stiff, and rough), the oxy-Hb concentration in the PFC area was lowest during tactile stimulation of smooth plants and highest during soft plant stimulation. Sex-based comparison of oxy-Hb concentrations showed significant differences in the overall PFC area for all four tactile treatment groups in males (p < 0.001). Specifically, when touching soft plants, the oxy-Hb concentration in females was significantly lower than that in males (p < 0.001). According to the SDM, the tactile stimulation of soft and smooth plants elicited the most relaxation, comfort, and favorable responses (p < 0.001). When touching smooth plants, the oxy-Hb concentration of the participant was the lowest, and according to the SDM, they reported the most soothing response. Summarily, the participants in the smooth plant group exhibited a trend of decreased oxy-Hb concentrations and concurrently experienced a sense of psychological stability. We established those tactile stimuli based on foliage texture resulted in different psychophysiological and psychological responses depending on the plant treatment group and sex.